Career development: A summer school cooperative education credit course for senior high school students - McLaughlin, George B. (Canadian Journal of Counselling and Psychotherapy, 2012)
The author in 1978 designed and taught a six-week course for credit for senior high school students. The course was listed in the North York summer school calendar in the usual way and taught in a school centrally located in the borough. Fourteen female and two male students enrolled. The curriculum for the course was obtained from the Ontario Ministry of Education publication Senior Guidance Guidelines 1977. The North York Co-operative Education Department arranged with the author for each student to work in an institution or commercialestablishment of his or her choice for one week without pay. The author visited each student at the work location at least once during the week. Class projects and a final examination were given. Two instruments were used to measure student growth: the Crites Vocational Maturity Inventory and the Secondary Self Concept Questionnaire developed by the North York Board of Education Research Department. Gains on these instruments between the first and last day of the course were significant at the .05 and .054 level respectively.